(untitled) (Nativa, 2024)
Metals’ high toxicity and ability to accumulate in soil and crops seriously threaten global food security. To address this, we need to expedite the restoration of agricultural lands that have been disturbed. Bioremediation, an effective treatment, relies on the ability of microorganisms to remove pollutants. Recent studies have shown that bacteria can serve as environmental sentinels, given their sensitivity to changing conditions and ability to adapt to adverse conditions. This study aimed to create a consortium based on microorganisms isolated from sediments from ten locations on the Euphrates River for applications in agricultural soil restoration areas. Six groups/species of bacteria were isolated, cultivated and evaluated: Burkholderia cepacia, Aeromonas hydrophila punctate, Klebsiella pneumonia, Aeromonas sorbia, Enterobacter aerogens e Rhizobium radiobacter in the removal of salts (Ca, Mg, SO4, Na and K) and heavy metals (Pb, Co, Cd, Cr, Zn, Fe, Mn, Ni and Cu). All bacteria showed good salt and heavy metal removal rates, where removal rates were obtained for 4 and 7 days ranging between (41.18287-61.31482), (42.03456-2.70738), (46.53214-64.75572), (48.55462- 8.30498), (42.94147-64.21361) and (26.65648-70.48373) respectively for the species above. Keywords: heavy metals; bioremediation by bacteria; contaminated soils; soil salinity; secondary metabolite; sediments of the Euphrates River. Biorremediação para melhorar a eficiência da recuperação de solos removidos de áreas de uso agrícola RESUMO: A elevada toxicidade dos metais e a sua capacidade de acumulação nos solos e nas culturas agrícolas representam uma séria ameaça à segurança alimentar mundial. Para resolver este problema, é necessário acelerar o ritmo de restauração das terras agrícolas que foram perturbadas. A biorremediação é um tratamento eficaz e depende da capacidade dos microrganismos de remover poluentes. Vários estudos recentes indicam que as bactérias podem ser sentinelas das mudanças ambientais, dada a sua sensibilidade às mudanças de condições e a sua capacidade de adaptação em condições adversas. Neste estudo objetivou-se criar um consórcio baseado em microrganismos isolados de sedimentos de dez locais do rio Eufrates, para aplicações em áreas de restauração de solos agrícolas. Foram isolados, cultivados e avaliados 6 grupos/espécies de bactérias: Burkholderia cepacia, Aeromonas hydrophila punctate, Klebsiella pneumonia, Aeromonas sorbia, Enterobacter aerogens e Rhizobium radiobacter, na remoção de sais (Ca, Mg, SO4, Na e K) e metais pesados ​​(Pb, Co, Cd, Cr, Zn, Fe, Mn, Ni e Cu). Todas as bactérias apresentaram boas taxas de remoção de sais e metais pesados, onde foram obtidas taxas de remoção para 4 e 7 dias variando entre (41.18287-61.31482), (42.03456-62.70738), (46.53214- 64.75572), (48.55462- 68.30498), (42.94147- 64.21361) e (26.65648- 70.48373) respectivamente para as espécies supracitadas. Palavras-chave: metais pesados; biorremediação por bactérias; solos contaminados; salinidade do solo; metabólito secundário; sedimentos do rio Eufrates.